Quantitative evaluation of China’s shipping decarbonization policies: The PMC-Index approach - Zhang, Qiang; Chen, Chen; Zheng, Jian; Chen, Liang (Frontiers in Marine Science, 2023)
In the past few decades, ship-source GHG emissions have increased significantly. As a large country with massive shipping activities, China has issued a number of governmental policies with the aim of promoting shipping decarbonization and achieving green shipping. This study adopts the Policy Modeling Consistency Index (PMC-Index) approach to quantitatively evaluate 15 representative policies that are dealing with shipping decarbonization affairs to different extents in China. The results show that there exists an overall good policy consistency with the average PMC index scoring 6.26, but all studied policies have certain aspects to be further improved. By reviewing these representative policies, it reveals that more emphasis has been placed by the Chinese government on the development and application of clean energy, coordination between shipping and port industries, and governance mechanism for shipping decarbonisation issues. In addition, two policy implications are draw for policy-makers in China.